Data for: Firth, JA. & Sheldon, BC. 2016. Social carry-over effects underpin trans-seasonally linked structure in a wild bird population. Ecology Letters; 10.1111/ele.12669 - Firth, J; Sheldon, B (University of Oxford, 2016)
This Data Supplements Firth, JA. & Sheldon, BC. 2016. Social carry-over effects underpin trans-seasonally linked structure in a wild bird population. Ecology Letters; 10.1111/ele.12669 http://onlinelibrary.wiley.com/doi/10.1111/ele.12669/full This Data Supplements Firth, JA. & Sheldon, BC. 2016. Social carry-over effects underpin trans-seasonally linked structure in a wild bird population. Ecology Letters; 10.1111/ele.12669 http://onlinelibrary.wiley.com/doi/10.1111/ele.12669/full